Preclinical study of innovative peptides mimicking the tertiary structure of the α-helix B of erythropoietin - Ivan V. Golubev; Vladimir V. Gureev; Mikhail V. Korokin; Maria A. Zatolokina; Elena V. Avdeeva; Anastasia V. Gureeva; Il'ya S. Rozhkov; Elena A. Serdyuk; Valeriya A. Soldatova (Belgorod National Research University, 2020)
Introduction: The aim of this study was to examine the effectiveness of innovative peptides obtained by addition of polypeptide motifs with antiaggregation activity (Arg-Gly-Asp, Lys-Gly-Asp and Pro-Gly-Pro) to a peptide mimicking the tertiary structure of the α-helix B of erythropoietin pHBSP (Pyr-Glu-Gln-Leu-Glu-Arg-Ala-Leu-Asn-Ser-Ser). Materials and methods: The cytoprotective activity of innovative peptides mimicking the tertiary structure of the α-helix B of erythropoietin at the doses of 5 μg/ml, 30 μg/ml and 50 μg/ml was studied on human endothelial cell culture in a simulated oxidative stress. An ADMA-like model of preeclampsia was simulated in the experiment. The study was conducted in 260 female Wistar rats, weighing 250-300 g. Results and discussion: Innovative peptides mimicking the tertiary structure of the α-helix B of erythropoietin retain their cytoprotective activity in a simulated oxidative stress in HUVEC cell culture at the doses of 5 μg/ml, 30 μg/ml, and 50 μg/ml. The compounds with laboratory codes P-αB1 and P-αB3 had the most pronounced cytoprotective activity. Administration of N-nitro-L-arginine-methyl ether to pregnant females for 7 days causes the morphofunctional changes similar to clinical changes in preeclampsia. The innovative peptide under laboratory code P-αB4 at the dose of 50 μg/kg mimicking the tertiary structure of the α-helix B of erythropoietin shows the most pronounced protective properties. Conclusion: Innovative peptides mimicking the tertiary structure of the α-helix B of erythropoietin have a pronounced positive influence on the morphofunctional disorders in animals with ADMA-like preeclampsia.